Assessment of Vitamin D Supplementation in People with Intellectual Disability - Zabalza, Ramón; Múgica, Iñaki; Sistiaga, Fernando; Garrido, Adolfo; Emparanza, José Ignacio; Zubillaga, Paul (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Vitamin D levels are often lower than recommended among certain groups, and these so-called at risk populations include institutionalised people with intellectual disabilities. The administration of vitamin D supplements does normalize these levels, but they tend to fall again when treatment is discontinued. The objectives of this study were, first, to assess whether the administration of 20,000 IU of cholecalciferol monthly and 60,000 IU quarterly over a year provide similar satisfactory results, and second, to explore whether the results are associated with following variables: sex, antiepileptic medication, being a wheelchair user or able to walk, and being a resident or day care user. The study population was composed of 204 individuals of both sexes cared for in four centres of the same institution. There were no differences between the levels reached with monthly and quarterly administration. The overall results show that, at the end of the test period, total 25(OH)vitamin D levels were <30 nmol/L in 3.5% of participants, 30 to < 50 nmol/L in 34%, 50 to <75 nmol/L in 41% and ≥75 nmol/L in 21.5%. There were significant differences between centres. We did not observe any harmful adverse effects attributable to the treatment. To conclude, we propose the continuous systematic administration of 60,000 IU of cholecalciferol every three months in this at-risk population.